Fully alive : the glory of God and the human creature in Karl Barth, Hans Urs von Balthasar, and theological exegesis of scripture /: the glory of God and the human creature in Karl Barth, Hans Urs von Balthasar, and theological exegesis of scripture. (2015 copyright 2015) - Fout, Jason A
No abstract available